2016
DOI: 10.5009/gnl15017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Steroid-Free Immunosuppressive Regimen after Liver Transplantation for Hepatocellular Carcinoma

Abstract: Background/AimsWe aimed to evaluate the efficacy and safety of an immunosuppressive regimen without steroids after liver transplantation (LT) for hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC).MethodsSixty-six HCC patients who underwent an immunosuppressive regimen without steroids after LT were enrolled in the steroid-free group. The preoperative characteristics and postoperative outcomes of these patients were compared with those of 132 HCC recipients who were placed on an immunosuppressive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…HBV‐infections might also occur in secrecy despite seronegative HBs‐Ag . It is supposed to be the result of immunosuppression, enhanced virus replication, extrahepatic reservoirs of HBV as well as direct stimulatory effects of prednisolone therapy on the HBV genome . Recent studies could show significantly fewer HBV‐recurrence in patients with steroid‐free regimens after LT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV‐infections might also occur in secrecy despite seronegative HBs‐Ag . It is supposed to be the result of immunosuppression, enhanced virus replication, extrahepatic reservoirs of HBV as well as direct stimulatory effects of prednisolone therapy on the HBV genome . Recent studies could show significantly fewer HBV‐recurrence in patients with steroid‐free regimens after LT .…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed to be the result of immunosuppression, enhanced virus replication, extrahepatic reservoirs of HBV as well as direct stimulatory effects of prednisolone therapy on the HBV genome . Recent studies could show significantly fewer HBV‐recurrence in patients with steroid‐free regimens after LT . The most important issue is the advent of effective NUC‐based prophylaxis, so that the impact of immunosuppression including corticosteroids is less dominant as it used to be.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention has been focused on the side effects associated with steroid-based IS regimens (6). Long-term steroids can facilitate the host immunity, which maybe the cause of HCC recurrence (7)(8)(9)(10). In addition, the numerous side effects of steroids, such as infections, obesity, lipid profile imbalances, hypertension and diabetes mellitus, have emphasized the need to avoid or limit steroid usage (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…(4,6,8) The majority of the studies using steroid-free regimens augmented their immune suppression with antibody induction therapy. (3,9,(19)(20)(21)(22)(23) Randomized trials that have used similar methodology and patient selection have provided conflicting evidence in regard to risk of ACR between cohorts using steroid versus steroid-free regimens. (5,7,15,24) Multiple meta-analyses and literature reviews have concluded that steroid-free immune suppression regimens lower the risk of NODAT, CMV infections, and hypercholesterolemia while having similar efficacy to steroid-based regimens in preventing ACR only when steroids were replaced with antibody induction treatments.…”
mentioning
confidence: 99%